2012
DOI: 10.1161/circinterventions.111.965608
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Effects of Elinogrel

Abstract: Background-Elinogrel is the only selective, competitive and reversible platelet P2Y 12 inhibitor available in both intravenous (IV) and oral formulations. Methods and Results-This substudy of the Intravenous and Oral Administration of Elinogrel to Evaluate Tolerability andEfficacy in Nonurgent Percutaneous Coronary Intervention patients (INNOVATE-PCI) trial evaluated the pharmacokinetic and pharmacodynamic effects of two dosing regimens of IV followed by oral elinogrel (120 mg IV plus 100 mg oral twice daily; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 22 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…This trial provided promising results of elinogrel in terms of platelet inhibition, as both intravenous and oral dosing achieved greater and more rapid platelet inhibition than clopidogrel, and safety, as no significant increase in major bleedings was found. 71,72 A safety concern was the presence of elevated liver enzymes in 4.0% and 4.8% of the elinogrel 100 mg and 150 mg twice daily arms, respectively, mostly within the first 60 days, compared with 1% in the clopidogrel group. Phase III clinical evaluation of elinogrel is still pending.…”
Section: Thromboxane a 2 Pathway Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial provided promising results of elinogrel in terms of platelet inhibition, as both intravenous and oral dosing achieved greater and more rapid platelet inhibition than clopidogrel, and safety, as no significant increase in major bleedings was found. 71,72 A safety concern was the presence of elevated liver enzymes in 4.0% and 4.8% of the elinogrel 100 mg and 150 mg twice daily arms, respectively, mostly within the first 60 days, compared with 1% in the clopidogrel group. Phase III clinical evaluation of elinogrel is still pending.…”
Section: Thromboxane a 2 Pathway Inhibitorsmentioning
confidence: 99%
“…Tato studie přinesla slibné výsledky elinogrelu ve smyslu inhibice krevních destiček, protože jak intravenózní, tak perorální podání vedlo k vyšší i rychlejší inhibici krevních destiček než v případě clopidogrelu, i k vyšší bezpečnosti, protože nebylo pozorováno významné zvýšení závažného krvácení. 71,72 Jisté obavy vyvolala přítomnost zvýšených koncentrací jaterních enzymů u 4,0 %, resp. 4,8 % pacientů v ramenech s elinogrelem v dávce 100 mg a 150 mg dvakrát denně, většinou v prů-běhu prvních 60 dní, oproti 1 % ve skupině s clopidogrelem.…”
Section: Inhibitory P2y 12unclassified
“…Cangrelor had additionally been used off-label as a bridging therapy before cardiac surgery after discontinuation of thienopyridines, offering the potential advantage of rapid reversal of antiplatelet action with discontinuation 1 hour before surgery. 40 Additional evidence suggests that the benefits of cangrelor are maintained across several high-risk subgroups, including those with a history of stroke ≥1 year from the time of PCI, older patients, and in those on a background of anticoagulant therapy with heparin, without concomitant increases in the rates of major bleeding. 4144…”
Section: Established Antiplatelet Therapiesmentioning
confidence: 99%
“…In a different conceptual approach, researchers have attempted to link high-risk cohorts and worsened clinical outcomes to the degree of platelet inhibition by individual tailoring of antiplatelet therapy. However, trials, such as the Gauging Responsiveness With A VerifyNow Assay-Impact on Thrombosis And Safety (GRAVITAS), 5 Testing Platelet Reactivity In Patients Undergoing Elective Stent Placement on Clopidogrel to Guide Alternative Therapy With Prasugrel (TRIGGER-PCI), 6 Intravenous and Oral Administration of Elinogrel to Evaluate Tolerability and Efficacy in Nonurgent Percutaneous Coronary Intervention Patients (INNOVATE-PCI), 7 Assessment by a Double Randomization of a Conventional Antiplatelet Strategy Versus a MonitoringGuided Strategy for Drug-Eluting Stent Implantation and of Treatment Interruption Versus Continuation One Year After Stenting (ARCTIC), 8 The Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes (TRIOLOGY-ACS), 9 and A Comparison of Prasugrel at PCI or Time of Diagnosis of Non--ST Elevation Myocardial Infarction (ACCOAST), 10 did not lend support to this notion. Lately, some differentiations emerged, for example, the insight by Salisbury et al 11 who have shown that the expected benefits and risks of prasugrel versus clopidogrel may depend on underlying patient characteristics.…”
mentioning
confidence: 99%